Resilience In Competition: Adapting Strategies For Lasting Advantage - Aprinawati Aprinawati; Sofialola Naibaho; Rendy Fachridan; Ahmad Siddik; Anggi Fuzi Nadia Sibuea (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
In the context of research exploring mental toughness in relation to athlete motivation and performance, findings demonstrate the significant role of mental toughness in influencing key aspects of athletes' lives. Mental toughness strategies have been proven to have an important impact in increasing athletes' motivation which then influences their performance in various types of sports. It is important for coaches and sports managers to consider mental toughness as an integral part of athlete training. Developing self-awareness and using certain psychological strategies can help athletes deal with pressure, manage anxiety, and maintain high motivation, all of which have the potential to improve their performance in competition. However, it should be noted that there is a need for more research and the development of more specific and measurable strategies to improve athletes' mental toughness. Although the literature highlights the importance of mental toughness, a deeper exploration of more effective and efficient strategies in building athletes' mental toughness is a valuable suggestion for the development of this science. The integration of these concepts in sports education programs can also provide significant benefits for athletes' development, both in the world of sport and in their daily lives.